1999
DOI: 10.1016/s0022-5347(01)61772-5
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Vascular Endothelial Growth Factor and Its Correlation With Bladder Cancer Recurrence Rates

Abstract: Our study demonstrates that VEGF is high in the urine of patients with bladder cancer and it correlates with tumor recurrence rates. VEGF is implicated in the pathogenesis of bladder cancer recurrence. Its quantification may provide a valuable noninvasive marker for the early detection of bladder tumor recurrence as well as a therapy target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
6

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(41 citation statements)
references
References 28 publications
0
35
0
6
Order By: Relevance
“…Analysis of miR expression exhibited a pattern of change consistent with pro-angiogenic phenotype, but miRs related to invasion were essentially unmodified in our UPK II-SV40 urothelial tumors. These data should be considered in the context of the controversial reports for the role of angiogenesis markers in predicting recurrence or invasion in clinical studies with superficial bladder carcinomas (11)(12)(13)52).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Analysis of miR expression exhibited a pattern of change consistent with pro-angiogenic phenotype, but miRs related to invasion were essentially unmodified in our UPK II-SV40 urothelial tumors. These data should be considered in the context of the controversial reports for the role of angiogenesis markers in predicting recurrence or invasion in clinical studies with superficial bladder carcinomas (11)(12)(13)52).…”
Section: Discussionmentioning
confidence: 93%
“…In this regard, some clinical studies have suggested that elevated microvessel density, an indicator of angiogenic phenotype, is associated with progression of carcinoma in situ to invasive cancer, but some other clinical observations did not confirm these results (11,12). Similar conflicting results have been reported for VEGF levels in urine or plasma (13) or for VEGF and HIF-1␣ expression in the tumor, which some authors suggest as important for progression to invasive cancer (14 -16). Most studies include both CIS and pT1a types of * This work was supported, in whole or in part, by National Institutes of Health Grants DK62987, DK55001, AA13913, DK61688, and CA125550 (to R tumors, thus making their interpretation confounding.…”
mentioning
confidence: 97%
“…The synthesis of cDNA was performed in a total volume of 20 l using 6 g of total RNA extracted from human liver (positive control for PPAR␣ and PPAR␥) and human kidney (positive control for PPAR␤) or 1 g of total RNA extracted from RT4 or T24 cells. The reaction was performed in the presence of 200 units of Moloney murine leukemia virus reverse transcriptase (M-MLV RT) (Invitrogen) and 0.5 g of oligo(dT) [12][13][14][15][16][17][18] (Invitrogen). Subsequent amplifications of the partial cDNA encoding hPPAR␣, hPPAR␤, and hPPAR␥ were performed using 6 l of reverse-transcribed mixture, which was one-third diluted as a template with specific oligonucleotide primers, as follows: hPPAR␣ sense, 5Ј-ACTCTGCCCCCTCTCGCCACTC-3Ј and antisense, 5Ј-GCCAAAGCTTCCAGAACTATCCTC-3Ј; hPPAR␤ sense, 5Ј-GAGCA-GCCACAGGAGGAAGCC-3Ј and antisense, 5Ј-GCTGTGGTCCCCCA-T-3Ј; hPPAR␥ sense, 5Ј-AGAGATGCCATTCTGGCCCAC-3Ј and antisense, 5Ј-GTGGAGTAGAAATGCTGGAGA-3Ј.…”
Section: Methodsmentioning
confidence: 99%
“…As shown in RT-PCR analysis using specific primers for hPPAR␣, hPPAR␤, and hPPAR␥ as described in detail under "Experimental Procedures." Specific cDNAs were synthesized from human liver and kidney RNA (positive controls), plasmids (positive controls), and from RT4 and T24 RNAs using oligo(dT) [12][13][14][15][16][17][18] in the presence of 200 units of Moloney murine leukemia virus reverse transcriptase. PCR products were resolved on a 1.5% agarose gel.…”
Section: Increased Ppar Agonist-dependent Stimulation Of Vegf Mrna Exmentioning
confidence: 99%
“…Es wurde bei 261 bzw. 40 Patienten nachgewiesen, dass Urin-VEGFWerte bei Harnblasenkarzinompatienten erhöht sind und eine Korrelation mit Rezidivrate und Tumorgrad besteht[147,148]. Keine Korrelation wurde zwischen VEGF-Expression und dem Überleben von Harnblasenkarzinompatienten beschrieben[142].Die Apoptose wird durch verschiedene Proteinfamilien reguliert, unter anderem dem pro-und antiapoptotischen Bcl2/ Bax-System.…”
unclassified